CONSTITUTIONAL RIGHT TO BE INFORMED TO AN ARRESTED PERSON FOR FAIR AND EFFECTIVE INVESTIGATION: COMPARATIVE STUDY BETWEEN MALAYSIA AND INDIA - Samsudin, Ifa Sirrhu Binti; Rajamanickam, Ramalinggam; Nordin, Rohaida Binti (The journal of contemporary issues in business and government, 2021)
The right to be informed is one of important right for the arrested person in pre-trial stage refers to various aspects of criminal procedure designed to safeguard the innocent from the harassment of the state authorities, both judiciary and executive. Each arrested person of the offence should be treated as an innocent person till been proved guilty by the court. Therefore, the arrested person has rights to be just, fair, reasonable, and effective investigation before deciding the cases as they will defense themselves during the investigation when they know what offences they alleged to. The United Nations contributed a lot in adopting declarations, conventions, and principles towards rights to justice in the court of law of the arrested person. Thus, this paper aim to discover how the right to be informed in fair and effective investigation applies in Malaysia and Indian criminal justice systems. This is important to see whether criminal justice system in Malaysia and India upholds the principles deemed necessary under constitutional rights. The researcher using doctrinal comparative method to emphasising the constitutional provisions which has been adopted in Malaysia and Indian Constitutions as well as their criminal procedure codes and in international convention and judgments of the courts. Right to be informed is the fundamental right of the arrested person in a criminal charge. In conclusion the necessity of discovering the truth is needed to apply the inappropriate procedures or methods and even may, sometime, infringe the fundamental rights of the arrested or any person involved, the liberty and jurisprudential concept of human rights in criminal justice must not be denied.